LEARNING SCIENCE PROCESS SKILLS (SPS) IN JUNIOR HIGH SCHOOL WATULIMO DURING THE PANDEMIC COVID-19 - Ericha Ayusepta Marviyani; Erman Erman (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2021)
This study aims to determine the application of learning science that involves science process skills (SPS) during the pandemic Covid-19. This research uses case study method with the research subject 5 science teacher and 15 students from 3 junior high school in Watulimo. The instrument of this study consists of questionnaire of teachers and students, with data collection techniques used were interviews, observation, and documentation. Results showed a decline in the application of SPS from learning offline to online. The decline is most obvious elements of the SPS integrated to formulating hypotheses, interpreting data, and conducting experiments with 1 of the 5 teacher respondents who apply it in science learning. These results indicate a low integrated SPS students. Factors that influence the low integrated SPS the term learning material used by teachers and not specific instruments to assess SPS. The results of this study as input for the junior high school science teacher to adjust the term learning material used to be used in online learning and special instruments to assess SPS (student worksheet that contain SPS material), so that students are able to develop.